Genetic diversity and toxin gene distribution among serovars of Actinobacillus pleuropneumoniae from Australian pigs. Issue 1 (29th January 2018) - Yee, S; Blackall, PJ; Turni, C
Abstract : Objective: To explore the diversity among isolates of the Actinobacillus pleuropneumoniae serovars most common in Australia (serovars 1, 5, 7 and 15) and to examine the Apx toxin profiles in selected representative isolates. Design: A total of 250 isolates selected from different farms were examined for their genotypic profiles and a subset of 122 isolates for their toxin profiles. Methods: The isolates of serovars 1, 5, 7 and 15 selected for this study came from different farms and different Australian states and were submitted for serotyping to the reference laboratory. The overall diversity of the strains was explored with the enterobacterial repetitive intergenic consensus (ERIC) PCR and the presence of the toxin genes was investigated with a toxin PCR assay. Results: Some degree of variation was observed in the ERIC‐PCR pattern within all four serovars, ranging from 38% to 61% genetic diversity. When looking at the toxin gene profile and, therefore, the predicted ability to produce the expected toxin pattern, one isolate each of serovars 1 (n = 20) and 7 (n = 47) and 17 isolates of serovar 15 (n = 40) showed variation to the expected gene profile. Conclusion: The variations in toxin gene patterns, as detected by PCR, found in this study could be related to significant changes in the gene sequence or total absence of the gene. Variation in toxin gene sequences has been observed in other countries. This variation in the toxin profile could also explain possible variation in pathogenicity observed in the field.